Colorectal cancer and Blastocystis sp. infection - Sulżyc-Bielicka, Violetta (Parasit Vectors, 2021)
BACKGROUND: Blastocystis sp. is a common intestinal protozoan found worldwide. Based on gene analysis, 17 subtypes (STs, ST1–ST17) have been identified, 9 of which have been isolated from humans. Differences in clinical consequences may depend on differences among the STs. Here, we evaluated the prevalence of Blastocystis sp. in patients with colorectal cancer (CRC) compared to a control group and assessed the relationships between Blastocystis sp. infection and sex; age; and CRC grade, stage, and location. METHODS: The study included 107 CRC patients (41 women and 66 men, median age 65 years); 124 subjects without colorectal cancer or a history of oncological disease comprised the control group (55 women and 69 men, median age 63). Stool samples were collected from patients before oncological treatment and examined using light microscopy (iodine-stained smear). Additionally, PCR-based identification of Blastocystis sp. was performed in 95 stool samples from CRC patients and 76 stool samples from the control group. RESULTS: Light microscopy showed that the prevalence of Blastocystis sp. was significantly higher in CRC patients than in the control group (12.15% and 2.42%, respectively; p = 0.0041). Multivariate analysis showed that the odds of Blastocystis sp. infection were fivefold higher in the CRC group than in the control group. PCR-based molecular examinations demonstrated that the proportion of patients infected with Blastocystis sp. was significantly higher in the CRC group than in the control group (12.63% and 2.63%, respectively; p = 0.023). The predominant ST in the CRC group was ST3, detected in nine patients (75%), followed by ST1 (2 patients, 16.7%) and ST2 (1 patient, 8.3%). No association was found between Blastocystis sp. infection and age, sex, or CRC stage, grade, or location. CONCLUSIONS: The results showed that CRC was associated with an increased risk of opportunistic Blastocystis sp. infection, even before oncological treatment. To the best of our knowledge, this is the first report estimating the prevalence of Blastocystis sp. infection in CRC patients before oncological treatment in Europe. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13071-021-04681-x.